Harm reduction in the hospital: An overdose prevention site (OPS) at a Canadian hospital. (1st October 2022) - Nolan, Seonaid; Kelian, Salpy; Kerr, Thomas; Young, Samantha; Malmgren, Isaac; Ghafari, Cher; Harrison, Scott; Wood, Evan; Lysyshyn, Mark; Holliday, Elizabeth
Abstract: Background: Substance use management in hospitals can be challenging. In response, a Canadian hospital opened an overdose prevention site (OPS) where community members and hospital inpatients can inject pre-obtained illicit drugs under supervision. This study aims to: (1) describe program utilization patterns; (2) characterize OPS visits; and (3) evaluate overdose events and related outcomes. Methods: A retrospective chart review was completed at one hospital in Vancouver, Canada. All community members and hospital inpatients who visited the OPS between May 2018 and July 2019 were included. Client measures included: hospital inpatient status, use of intravenous access line for drug injection, and substances used. Program measures included: number of visits (daily/monthly), overdose (fatal/non-fatal) events and overdose-related outcomes. Results: Overall, 11, 673 OPS visits were recorded. Monthly visits increased from 306 to 1198 between May 2018 and July 2019 respectively. On average, 26 visits occurred daily. Among all visits, 20% reported being a hospital inpatient, and 5% reported using a hospital intravenous access line for drug injection. Opioids (56%) and stimulants (24%) were the most common substances used. Overall 39 overdose events occurred - 82% required naloxone reversal, 28% required transfer to the hospital's emergency department and none were fatal. Overdose events were more common among hospital inpatients compared to community clients (6.6 vs 2.2 per 1000 visits respectively; p value = 0.046). Conclusions: This unique OPS is an example of a hospital-based harm reduction initiative. Use of the site increased over time among both groups with no fatal overdose events occurring. Highlights: Substance use management in hospitals can be challenging. To address this, one Canadian hospital opened an Overdose Prevention Site (OPS). Between May 2018 and July 2019, 11, 673 visits occurred at the OPS. 39 overdose events occurred – 82% required reversal with naloxone. Use of the OPS increased over time and no fatal overdoses occurred.